Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1039/d0tb01643h
|View full text |Cite
|
Sign up to set email alerts
|

Shape-transformation of polymersomes from glassy and crosslinkable ABA triblock copolymers

Abstract: We used osmotic pressure changes to induce shape transformation in glassy polymersomes from crosslinkable ABA triblock copolymers. We observed that both the speed of osmotic pressure changes and order of crosslinking affect shape change behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Recently, our group reported the shape transformation of glassy polymersomes from ABA triblock copolymers via a combination of osmotic pressure changes and crosslinking. 45 Using polymersomes assembled from PEG-block-poly(coumarin methacrylate)-stat-PS-block-PEG, we observed that, when exposed to osmotic pressure changes via dialysis, these vesicles only showed a size decrease but maintained their spherical morphology (Fig. 5(b)).…”
Section: Osmotic Pressure and Concentration Gradientsmentioning
confidence: 95%
“…Recently, our group reported the shape transformation of glassy polymersomes from ABA triblock copolymers via a combination of osmotic pressure changes and crosslinking. 45 Using polymersomes assembled from PEG-block-poly(coumarin methacrylate)-stat-PS-block-PEG, we observed that, when exposed to osmotic pressure changes via dialysis, these vesicles only showed a size decrease but maintained their spherical morphology (Fig. 5(b)).…”
Section: Osmotic Pressure and Concentration Gradientsmentioning
confidence: 95%
“…Advances in precise block copolymer synthesis (i.e., molecular weight control, end-group fidelity, monomer selection) have led to tailorable interfacial curvature and block copolymer asymmetry that generate predictable morphologies and nanostructure organization. 13 For a given amphiphilic block copolymer system, adjustments in block volume fraction and nature (i.e., glassy 14,15 vs. soft) can generate a plethora of morphologies in dilute aqueous environments-including spherical or cylindrical micelles, 16,17 network phase and bilayers/vesicles. 18 The introduction of stimuli-responsive motifs to these self-assembled systems, such as photoresponsive functional groups (i.e., azobenzene, 19,20 o-nitrobenzene, 21 ) temperature-responsive blocks (i.e., poly(N-isopropylacrylamides), 22,23 or even so-called rigid-flexible blocks, 24 grant access to incredibly versatile and responsive nanoobjects.…”
Section: Introductionmentioning
confidence: 99%
“…In the initial phase spanning from 1999 to 2009, shape transformation of polymer vesicles was successfully induced without the use of biological shape-modulating factors, for instance, transformation from a tubule to a vesicle by osmotic pressure, tubule generation by optical tweezers, and destruction of a vesicle by light irradiation (Table ). , The subsequent phase starting in 2010 witnessed the emergence of controlled shape transformation and the identification of different deformation pathways (Figure b). Spherical vesicles have been transformed into a variety of nonspherical shapes including a disc, stomatocyte (sto), nest, sto-in-sto, tubule, disc with tubular arms, tubule with sto, etc. Although more and more shapes have been accessed, shape transformation of polymer vesicles still lies in the trial-and-error stage.…”
Section: Introductionmentioning
confidence: 99%